2021
DOI: 10.2147/ppa.s306498
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Neurologist Preferences in the United States for Relapsing-Remitting Multiple Sclerosis Treatments: Findings from a Discrete Choice Experiment

Abstract: Background and Objective Relapsing-remitting multiple sclerosis (RRMS) is a chronic inflammatory disease associated with central nervous system dysfunction and accelerated brain volume loss (BVL). There exists a paucity of research examining the importance of BVL to patients and neurologists and exploring whether such preferences may differ between these two groups. This study sought to evaluate the preferences of patients and neurologists for RRMS treatments by considering benefits and risks asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…When considering DMT treatment initiation, the attributes of efficacy, mode and frequency of administration, and side effect profiles are valued most by patients, according to a systematic review of 24 DMT studies in RRMS [ 51 ]. However, a USA-based survey of 150 patients and 154 neurologists, and a Dutch survey of 62 HCPs, found that HCPs may view logistical factors surrounding receipt of treatment as less important, and instead focus on prevention of disease (brain volume loss, relapse rate) and disability progression, as well as treatment safety, including risk of infection [ 48 , 52 ]. The MS in the 21st Century initiative of 14 HCPs and 11 patients with MS from Europe and the USA revealed that HCPs were concerned about the level of risk patients were willing to accept with their therapy [ 49 ].…”
Section: Overcoming Barriers To Sdmmentioning
confidence: 99%
“…When considering DMT treatment initiation, the attributes of efficacy, mode and frequency of administration, and side effect profiles are valued most by patients, according to a systematic review of 24 DMT studies in RRMS [ 51 ]. However, a USA-based survey of 150 patients and 154 neurologists, and a Dutch survey of 62 HCPs, found that HCPs may view logistical factors surrounding receipt of treatment as less important, and instead focus on prevention of disease (brain volume loss, relapse rate) and disability progression, as well as treatment safety, including risk of infection [ 48 , 52 ]. The MS in the 21st Century initiative of 14 HCPs and 11 patients with MS from Europe and the USA revealed that HCPs were concerned about the level of risk patients were willing to accept with their therapy [ 49 ].…”
Section: Overcoming Barriers To Sdmmentioning
confidence: 99%
“…Familiarity with established DMTs is an influential factor and can result in treatment inertia (reported in up to 70% of neurologists) and delays switching from an established to a newer therapy, especially among non-MS neurologists [ 127 , 136 ]. In the US, HCPs might be even more risk averse than patients due to different perspectives and clinical experience regarding potentially life-threatening safety risks, which can encourage more defensive medical practices out of concern for legal liability [ 137 , 138 ]. Updated long-term safety profiles, which can be communicated through continuing medical education and peer-to-peer events [ 10 , 139 ], will be critical for managing perceptions of HCPs and non-specialist neurologists in this regard.…”
Section: Barriers To Adoption Of Early Hets and Potential Solutionsmentioning
confidence: 99%
“…Shared decision-making between HCPs and patients is a key component to improving acceptance of, and adherence to, DMTs [ 56 , 127 ]. It also allows patients to communicate their preferences, which may differ from those of HCPs [ 137 , 138 , 169 ]. For instance, route of administration is an important consideration for many patients [ 182 ].…”
Section: Barriers To Adoption Of Early Hets and Potential Solutionsmentioning
confidence: 99%
“…Two thirds of the patients are female [7]. In this study, people with MS (pwMS) were selected as a target group, since MS is a typical preferencesensitive condition, in which there are multiple treatments with similar efficacy but different safety profiles, follow-up and administrations [8]. The aim of the present study was to evaluate what type of information pwMS use in SDM and what are the sources of that information.…”
Section: Introductionmentioning
confidence: 99%